-4-7f=-6f-3

Simple and best practice solution for -4-7f=-6f-3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -4-7f=-6f-3 equation:



-4-7f=-6f-3
We move all terms to the left:
-4-7f-(-6f-3)=0
We get rid of parentheses
-7f+6f+3-4=0
We add all the numbers together, and all the variables
-1f-1=0
We move all terms containing f to the left, all other terms to the right
-f=1
f=1/-1
f=-1

See similar equations:

| x-(0.25x)=1,000 | | 20=7y+-y | | –5(7+x)=x–39 | | -14+n=5 | | N-246=605-(4x28) | | -0.9(h-3)=-0.99 | | 4x=2x+38 | | 8n−​(6n+5​)=9 | | 2(y-3)+2=8 | | -4(2x+5)+2x+3=−-11 | | -4=u/2-7 | | 10b+18=  28 | | 3x+3-6x+3=-3x+6 | | -6y-2=-4(y+2) | | -76=-3b49 | | 4(z-6)=5 | | 4x-12/16=-2 | | 6p-91=117 | | 3(x+2)-1=(2x+3)-7 | | 24n+3​=12n−5​ | | (x−3)/4−(x+8)/6=(5x−3)/9 | | 3(x-2)-4(x+3)=5-x | | x−3/4−x+8/6=5x−3/9 | | 4v+2.4=14.88 | | c-2=14-7c | | c/2+44=66 | | X=122x–x+25-x | | −3x−5=18 | | 2(3x+60=18 | | 2y+6^=94 | | 72+(4x+8)=180 | | 5(y-3=30) |

Equations solver categories